2021
DOI: 10.1111/hequ.12302
|View full text |Cite
|
Sign up to set email alerts
|

How do university systems' features affect academic inbreeding? Career rules and language requirements in France, Germany, Italy and Spain

Abstract: Studies on academic inbreeding have mostly focused on institutional inbreeding and its negative effects, whereas little research has explored its causes. We identify current explanations of the macro-, meso-and micro-level factors that sustain academic inbreeding as well as research gaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
(85 reference statements)
0
10
0
1
Order By: Relevance
“…For example, Spanish, Italian, and US researchers share similar problems and concerns (at least regarding the presence of QRPs). However, crucial elements such as the academic job market structure, R&D investment levels, or the academic structure vary across countries (Seeber & Mampey, 2021 ), particularly when comparing the US and its European counterparts (UNESCO, 2021). Therefore, country-specific policies should be developed in each case to ensure that the issues mentioned above are ameliorated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Spanish, Italian, and US researchers share similar problems and concerns (at least regarding the presence of QRPs). However, crucial elements such as the academic job market structure, R&D investment levels, or the academic structure vary across countries (Seeber & Mampey, 2021 ), particularly when comparing the US and its European counterparts (UNESCO, 2021). Therefore, country-specific policies should be developed in each case to ensure that the issues mentioned above are ameliorated.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, Spanish academia is a system transitioning towards an empirically oriented research culture (Fernández-Quijada & Masip, 2013 ; Rodríguez-Gómez & Goyanes, 2020 ), illustrative of several similar research contexts (e.g., Italy). In this sense, the Spanish and Italian research systems share many common characteristics (e.g., closed research job markets that favor local researchers) not found in Anglo-Saxon academic contexts (Seeber & Mampey, 2021 ).Secondly, Spanish researchers could be particularly susceptible to QRPs and problematic incentives due to the adverse effects of the 2008 economic crisis on Spanish academia: increased job instability, unemployment, and the exacerbation of a publish-or-perish culture (Rodríguez-Gómez & Goyanes, 2020 ). Thirdly, Spanish researchers might show a high sensitivity to academic rewards (as illustrated with Spain being the second most efficient country in research spending; Nature, 2020 ).…”
mentioning
confidence: 99%
“…Thus, financially and geographically disadvantaged universities may choose to employ their own graduates as a suitable option (Pan, 1993). In some disciplines and regions, language requirements contribute substantially to academic inbreeding (Seeber & Mampaey, 2021).…”
Section: Benefits and Risks Of Academic Inbreedingmentioning
confidence: 99%
“…Jones and Jefferson (2021) argue that three distinct, but complementary concepts may be used to explain the existence or absence of academic inbreeding in higher education systems: internal and external academic labour markets, vertical stratification, and social and cultural capital. Seeber and Mampaey (2021) explore the causes of academic inbreeding in European higher education systems, and argue that macro-level factors, such as career rules designed to guarantee quality and language requirements, represent barriers to attract international scholars and to promote multidisciplinary engagement, while contributing to the formation and prevalence of academic inbreeding. Macfarlane and Jefferson (2021) use a historical perspective to argue that academic inbreeding should be understood relative to the rules of medieval guilds, in the sense that such as it was the case in medieval guilds, the path of academic inbreeds relates to having access (privilege) to specific academic career entrance pathways.…”
Section: The S Tud Ie S and A B Rief Summary Of Their Find Ing Smentioning
confidence: 99%